Cholinergic Denervation Patterns Across Cognitive Domains in Parkinson's Disease. Issue 3 (2nd November 2020) - van der Zee, Sygrid; Müller, Martijn L.T.M.; Kanel, Prabesh; van Laar, Teus; Bohnen, Nicolaas I.
ABSTRACT: Background: The cholinergic system plays a key role in cognitive impairment in Parkinson's disease (PD). Previous acetylcholinesterase positron emission tomography imaging studies found memory, attention, and executive function correlates of global cortical cholinergic losses. Vesicular acetylcholine transporter positron emission tomography allows for more accurate topographic assessment of not only cortical but also subcortical cholinergic changes. Objective: The objectiveof this study was to investigate the topographic relationship between cognitive functioning and regional cholinergic innervation in patients with PD. Methods: A total of 86 nondemented patients with PD (mean ± SD age 67.8 ± 7.6 years, motor disease duration 5.8 ± 4.6 years), and 12 healthy control participants (age 67.8 ± 7.8 years) underwent cholinergic [ 18 F]Fluoroethoxybenzovesamicol positron emission tomography imaging. Patients with PD underwent neuropsychological assessment. The z scores for each cognitive domain were determined using an age‐matched, gender‐matched, and educational level–matched control group. Correlations between domain‐specific cognitive functioning and cholinergic innervation were examined, controlling for motor impairments and levodopa equivalent dose. Additional correlational analyses were performed using a mask limited to PD versus normal aging binding differences to assess for disease‐specific versus normal aging effects. Results: Voxel‐based whole‐brain analysis demonstrated partial overlapping topography across cognitive domains, with most robust correlations in the domains of memory, attention, and executive functioning ( P < 0.01, corrected for multiple comparisons). The shared pattern included the cingulate cortex, insula/operculum, and (visual) thalamus. Conclusion: Our results confirm and expand on previous observations of cholinergic system involvement in cognitive functioning in PD. The topographic overlap across domains may reflect a partially shared cholinergic functionality underlying cognitive functioning, representing a combination of disease‐specific and aging effects. © 2020 International Parkinson and Movement Disorder Society